SAT0087 Serum Levels of CXCL13 Refine The Predictive Ability of Autoantibodies To Identify Unstable Remission in Early Rheumatoid Arthritis. (15th July 2016) - Bugatti, S.; Manzo, A.; Vitolo, B.; Benaglio, F.; Caporali, R.; Montecucco, C.
Abstract : Background: Early achievement and maintenance of disease remission improve long-term outcomes in patients with rheumatoid arthritis (RA), and eventually allow therapeutic withdrawal. Better knowledge of the prevalence and prognostic factors for sustained remission might improve patient care according to their individual profile. RA-specific autoantibodies are associated with a less favorable disease course, but their impact on the achievement and sustainability of remission upon treatment in early RA remains controversial. Objectives: To evaluate whether additional B cell-related markers, such as serum levels of the B-cell chemoattractant CXCL13, predict different remission outcomes in patients with early RA. Methods: We evaluated 205 RA patients from the Pavia early arthritis inception cohort not in remission at baseline with at least 2 years of follow-up, for whom baseline serum was available. Patients had arthritis of short duration (<12 months) and were treatment-naïve at presentation. After diagnosis, patients were initiated a treat-to-target regimen with methotrexate aiming at low disease activity and were seen at 2-months intervals for the first six months and then trimestrally. Levels of rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPA) and CXCL13 were determined on baseline sera. Point remission was defined as the achievement of DAS28 remission (<2.6) or SDAI remission (≤3.3) at any time within the first 12 months. Mean DAS28 <2.6 and mean SDAI ≤3.3 in the 3 visits following first remission (7–9 months) were regarded as sustained remission. Results: 95/205 (46.3%) patients achieved point DAS28 remission and 69/205 (33.7%) point SDAI remission, with a median (IQR) time to remission of 6 (2–9) and 6 (4–9) months respectively. Male gender, younger age, a lower TJC28, better functional status, absence of radiographic erosions and use of prednisone were independent predictors of point remission. No significant effects of the autoantibody status and CXCL13 levels, alone or in combination, were seen. Irrespective of the remission criterion, more than half of the patients lost remission at follow-up (54.7% for DAS28, 62.3% for SDAI). Shorter time to remission and deeper remission were independent predictors of sustained remission (Figure 1 ). The ACPA status did not significantly impact the chance of sustaining remission. In contrast, both DAS28 and SDAI remission showed a trend to be less frequently maintained in RF-positive patients and in patients with baseline serum levels of CXCL13 >100 pg/ml (Figure 1 ). The combination of RF-positivity and high CXCL13 independently predicted failure to sustain remission with an adjusted OR (95% CI) of 8.49 (1.95 to 36.91) for DAS28 and 4.61 (1.01 to 24.67) for SDAI (Figure 1 ). Conclusions: Disease remission is unfrequently maintained in early RA patients despite steered treatment strategies. B-cell autoimmunity does not significantly impact the chance of ever achieving remission. However, RF-positivity in combination with high CXCL13 identify a subgroup of patients at particularly high risk of losing remission in the short-term, irrespective of how early and how stringent remission is achieved. Disclosure of Interest: None declared